When does economic development promote mitigation and why? - Clulow, Zeynep (Taylor & Francis, 2016)
Is economic development compatible with mitigation? On the one hand, development should promote effective climate policy by enhancing states’ capacities for mitigation. On the other hand, economic growth creates more demand for production, thereby inhibiting emissions reduction. These arguments are often reconciled in the environmental Kuznets curve (EKC) thesis. According to this approach, development initially increases emissions in poor economies, but begins to lower emissions after a country has attained a certain level of development.